The implementation of complex social policy: Institutional layering and unintended consequences in the National Disability Insurance Scheme. Issue 4 (29th April 2019) - Nevile, Ann; Malbon, Eleanor; Kay, Adrian; Carey, Gemma
Abstract: In this article, we identify the unfolding unintended consequences which flow from one instance of policy layering in Australia's National Disability Insurance Scheme (NDIS). We show how use of a causal diagram, which highlights feedback loops and emergent properties, to map complex chains of causal factors can assist policy scholars and policy practitioners to understand the likely direction of change and possible responses. In the case of Australia's National Disability Insurance Scheme, our analysis suggests that the likely direction of change will work against two of the fundamental design features of the NDIS: providing participants with more choice and control, and ensuring all eligible Australians are able to access appropriate services and supports regardless of where they live. Our analysis points to the use of price regulation as the site of potential intervention because of the role it plays in subsequent feedback loops and the development of the two, unwelcome, emergent properties. Abstract : This article analyses the likely direction of change and possible responses which flow from implementation decisions in the NDIS. Our analysis suggests the likely direction of change will limit opportunities for all participants to exercise choice as well as decreasing equity of access to high quality disability support services.